Evidence of habitat structuring Aedes albopictus populations in Réunion Island. - Hélène Delatte (Public Library of Science (PLoS), 2013)
Arbovirus vector dynamics and spread are influenced by climatic, environmental and geographic factors. Major Chikungunya and Dengue fever outbreaks occurring the last 10 years have coincided with the expansion of the mosquito vector Aedes albopictus to nearly all the continents. We characterized the ecological (larval development sites, population dynamics, insemination and daily survival rates) and genetic (diversity, gene flow, population structure) features of two Aedes albopictus populations from distinct environments (rural and urban) on Réunion Island, in the South-West Indian Ocean. Microsatellite analysis suggests population sub-structuring Ae. albopictus populations. Two genetic clusters were identified that were significantly linked to natural versus urban habitats with a mixed population in both areas. Ae. albopictus individuals prefer urban areas for mating and immature development, where hosts and containers that serve as larval development sites are readily available and support high population densities, whereas natural environments appear to serve as reservoirs for the mosquito.